Designing a wireless robot plotter as a supporting tool for understanding logical thinking - Aan Darmawan H; Ratnadewi Ratnadewi; Agus Prijono (Jurnal Mantik, 2023)
OSTR stands for Open Source Turtle Robot is a turtle robot whose hardware and software are open source and published by MakersBox located in Adair Village, OR, United States of America. In this study OSTR will be developed into an Wireless Robot Plotter that can draw and write and is equipped with computer software to support the needs of the learning process in understanding logical thinking for students. In this study, a wireless Robot Plotter design has been successfully designed to support students' understanding of logical thinking. A logical thought in the form of syntactic logic steps "turtle graphics" is inserted into the application interface (created in visual basic language), then the logic steps are translated in the form of an image that can be viewed on the monitor screen and sent wirelessly to the Robot Plotter (using nodeMCU ESP8266-12 as the processor) to be drawn by the Robot Plotter. From the tests, the realized wireless Robot Plotter successfully drew according to the logic steps instructed through the created interface application. The research urgency is to train logical thinking by designing a robot plotter so that abilities and skills are sharpened and the plotter robot used to draw basic batik motifs can be utilized by the creative industry.